2002
DOI: 10.1002/cncr.10839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HER‐2/neu expression in prostatic adenocarcinoma

Abstract: BACKGROUNDSome evidence suggests a role for HER‐2/neu overexpression in prostate carcinoma progression. Reported rates of HER‐2/neu overexpression in patients with prostate carcinoma vary greatly.METHODSThe authors studied radical prostatectomy specimens from 38 patients who had biochemical failure after undergoing radical prostatectomy for prostate carcinoma. Immunohistochemistry for HER‐2/neu overexpression using the HercepTest kit (Dako Corporation, Carpenteria, CA) was employed. Two different antigen‐retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…We observed intense and selective overexpression of c-erb B2 in these areas, this being the first report of such pattern in CS. This is an immunohistochemical feature seldom reported in conventional prostatic adenocarcinoma [27], but interestingly present in our two patients.…”
Section: Discussionmentioning
confidence: 69%
“…We observed intense and selective overexpression of c-erb B2 in these areas, this being the first report of such pattern in CS. This is an immunohistochemical feature seldom reported in conventional prostatic adenocarcinoma [27], but interestingly present in our two patients.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, despite recent advances in PCa research and in part due to the lack of suitable cell models, the role of ErbB-2 vs. EGFR in androgen-stimulated proliferation is still not fully understood. Furthermore, the investigation on the role of EGFR and ErbB-2 activation and/or overexpression in the development of CR PCa cells is inconsistent [14–20]. Therefore, in the present study, we used two independent in vitro cell models which respectively include AS and CR cells and recapitulates clinical PCa progression from AS to CR stage to determine the role of EGFR vs. ErbB-2 activation in androgen-stimulated proliferation and CR PCa cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, other studies showed higher levels of ErbB-2 protein in some prostatic tumors than normal controls [1719]. Analyses of clinical specimens showed that ErbB-2 protein may be elevated in a subset of CR PCa [2023]. Conversely, inhibition of ErbB-2 results in the suppression of xenograft tumor growth and decreases AR transcriptional activity [24, 25].…”
Section: Introductionmentioning
confidence: 95%
“…In prostate cancer, Her2/ neu (HER2) over expression is reported to high [54,55,56]. Patients with HER2 positive (2+ or higher on IHC) cancers have better survival and lower relapse rates as compared to the HER2 negative prostate cancers [57].…”
Section: Armed Activated T Cell (Atc) Therapy-her2 “Positive” Crpcmentioning
confidence: 99%